Analysis of the Influence Health Team's Performance on the Quality of Emergency Services at PSC 119 Takalar District - A. Rizki Amelia; Triska Ayu Fitriani; Nurmiati Muchlis; Feby Triadi (Program Pascasarjana Universitas Negeri Makassar, 2023)
The performance of medical personnel is obtained by comparing the results of carrying out one's duties in a certain period and is used to measure the results of medical personnel's achievements Emergency means life threatening, while emergency is the need to get immediate treatment or action to eliminate the threat to the victim's life. This study aims to find out the influence of the health team's performance on the quality of emergency services at the Public Safety Center (PSC) 119 Takalar. This study used quantitative research with a Cross Sectional Study design. The population was the entire PSC 119 health team in Takalar. The sampling technique used was Total Sampling. The results of this study reported that punctuality had a direct significant and positive influence on service quality , effectiveness demonstrated a direct significant and positive influence on service quality, independence illustrated a direct significant and positive influence on service quality and work commitment showed a direct significant and positive influence on service quality. This study concluded that (1) punctuality had an influence on the quality of emergency services at PSC 119 Takalar, (2) Effectiveness confirmed an influence on the quality of emergency services at PSC 119 Takalar, (3) independence showed an influence on the quality of emergency services at PSC 119 Takalar, (4) work commitment illustrated an influence on the quality of emergency services at PSC 119 Takalar (5) demonstrated effectiveness an influence of 17,847 times on the quality of emergency services in PSC 119 Takalar.